(untitled) (American Journal of Technology and Applied Sciences, 2023)
For the last several decades, humanity has been experiencing an information crisis. It is getting stronger year by year and entering many areas of human activity. Today, cartographers use information from many sources to create topographical and geographic maps and atlases, to decipher aerial and space images, to process the results of field measurements, and to present information in web form in computer systems.